2010
DOI: 10.1021/ja107847d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Lysine Side-Chain Amino Groups in a Protein Studied by Heteronuclear 1H−15N NMR Spectroscopy

Abstract: Despite their importance in macromolecular interactions and functions, the dynamics of lysine side-chain amino groups in proteins are not well understood. In this study, we have developed the methodology for the investigations of the dynamics of lysine NH3(+) groups by NMR spectroscopy and computation. By using 1H−15N heteronuclear correlation experiments optimized for 15NH3(+) moieties, we have analyzed the dynamic behavior of individual lysine NH3(+) groups in human ubiquitin at 2 °C and pH 5. We modified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
137
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(150 citation statements)
references
References 85 publications
12
137
1
Order By: Relevance
“…5 For ubiquitin, the majority of the lysine NH 3 þ groups display notably low S 2 order parameters, reflecting a high degree of internal mobility for these functionally important entities, with correlation times in the subnanosecond range for the NH 3 þ bond rotations. However, the origin of the side-chain mobility could not be elucidated from experiment alone.…”
Section: B S Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…5 For ubiquitin, the majority of the lysine NH 3 þ groups display notably low S 2 order parameters, reflecting a high degree of internal mobility for these functionally important entities, with correlation times in the subnanosecond range for the NH 3 þ bond rotations. However, the origin of the side-chain mobility could not be elucidated from experiment alone.…”
Section: B S Supporting Informationmentioning
confidence: 99%
“…13 To ensure a fair comparison, the simulation was run at the same temperature as in the experiment; otherwise, the MD simulation protocol was the same as described previously. 5 The length of the MD simulation was expected to be adequate for this analysis, since our previous NMR relaxation study showed that the reorientation of the symmetry axes of lysine NH 3 þ groups in ubiquitin occurs on the subnanosecond time scale. 5 Values of AE 3 J NζCγ ae were calculated from 1000 MD snapshots sampled every 1 ns.…”
Section: B S Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] Use of short-and long-range 15 C/ 15 N correlation in the lysine side chain in ubiquitin. [21,65] One of them is the intra-residue 15 N z and 13 C g coupling while the other is between the 15 N z and carbonyl 13 C across a hydrogen bond, as shown in Figure 6 J NzCg values are also calculated from the experimental 3 J NzCg and torsional angles obtained from the crystal structure by employing the empirical Karplus equation.…”
Section: Conformational and Configurational Analysismentioning
confidence: 99%
“…[19] It also provides the signature of the hydrogen bond in either small or medium-sized molecules such as benzamide [20] and its related compounds or the side-chain residue of protein molecules, thereby giving access to dynamic information about the protein side chains. [21] It has also received considerable attention in recent times in establishing configurations of bigger molecules. [22] Herein, we mainly focus on recent experimental methods designed for the measurement of n J XY , with special emphasis on n J CH , their applications and recent theoretical developments.…”
Section: Introductionmentioning
confidence: 99%